Modeling Cardiac Congenital Diseases: From Mathematic Tools to Human Induced Pluripotent Stem Cells. (12th May 2014) - Iop, Laura
Abstract : Cardiac congenital diseases are rare inherited disorders characterized by anatomical malformations and/or by electrophysiological abnormalities, both affecting the whole heart function. In order to clarify the underlying pathophysiological mechanisms, experimental modeling has been proposed through in silico, in vitro, and/or in vivo simulations. Bioinformatics, transgenesis, heterologous expression systems, mammalian models, and, recently, pluripotent stem cells have been advanced to effectively recapitulate several human congenital diseases (such as Brugada syndrome, CPVT, LQTs, and ARVC) and, potentially, provide new insights into their pathomechanisms for novel therapeutic perspectives.